Digital Transformation in Taxation Systems: A Systematic Literature Review - Dinda Chairunissa; Milla S. Setyowati (Ekonomis: Journal of Economics and Business, 2026)
Digital transformation in tax administration has become a priority strategy in various countries to improve efficiency, transparency, and compliance. This study conducted a Systematic Literature Review (SLR) of 14 empirical articles published between 2020 and 2025 to synthesize the current knowledge on the application of digital technology in tax systems. The review explored key themes, including drivers of technology adoption (such as perceived usefulness, trust, and digital readiness), barriers (such as privacy issues, infrastructure limitations, and system complexity), theoretical frameworks used (TAM, UTAUT, TOE, and Signaling Theory), and the impact of digitalization on tax compliance. Most studies demonstrated increased accessibility, increased freedom, and administrative efficiency, but some also noted limited or negative impacts due to weak institutional capacity and weak law enforcement. The study also identified important gaps in the literature, such as a lack of longitudinal studies, a lack of exploration of frontier technologies (such as blockchain and ethical AI), and low representation from developing countries. Based on these findings, this study presents an integrative conceptual framework and recommends policies for building an adaptive, credible, and data-driven digital tax system.